Effects of School Environmental Factors on Girl-Child Stay in School in Primary Schools in Busoba Sub County Mbale District - Musame Zachary (Uganda Christian University, 2024)
The purpose of this study was to establish effects of school environmental factors on girl child stay in school in Busoba sub county, Mbale district. The study was guided by the following specific objectives; to establish how teacher-pupil relationship affects girl-child stay in primary schools in Busoba Sub County, Mbale district; to find out how sanitation facilities affect girl-child stay in primary schools in Busoba Sub County, Mbale district; and to investigate how school location affects girl-child stay in primary schools in Busoba Sub County, Mbale district. The study used a descriptive survey design. The design was chosen on the rationale that it could be carried out within a short period of time since it was cross sectional. The Target population was 283, which comprised 74 teachers and 209 pupils. The study used simple random sampling to select pupils from primary six from the target schools. Stratified sampling was used to cater for gender differences. The total sample was 191 respondents, comprising 132 pupils and 59 teachers. The researcher used questionnaires to collect data from 132 pupils. The researcher collected data from 59 teachers using interview guides. The quantitative data was analyzed and tabulated using descriptive statistics including frequency tables and percentages. The qualitative data was processed through thematic analysis. The findings show that teacher-pupil relationship and girl-child stay in primary schools are linked. A total of 67% of the respondents agreed that teachers can motivate girls to stay in school. This is possible when teachers encourage girls to stay in school, to form good peer groups and to keep consulting teachers for guidance. Girls are able to stay in school once there are sufficient toilet facilities. They feel comfortable if they are able to help themselves in privacy, without interference from the boys. During menstruation period, girls need safer and secure sanitation facilities. These enable girls to stay in school. The findings show that schools that are easily accessible increase girl-child stay in school. Girls tend to tire easily on their way to school. Schools which are located within the easy reach of the girl-child tend to favour them in terms of regular school attendance. Basing on the findings, this study concludes that there is a strong relationship between teacher-pupil relationship and girl-child stay in primary schools. This is possible when teachers encourage girls to stay in school, to form good peer groups and to keep consulting teachers for guidance. The study further concludes that girls are able to stay in school once there are sufficient toilet facilities. Basing on the findings, schools that are easily accessible increase girl-child stay in school. Once schools are near girls’ homes, there are chances that they can attend daily, have the midday meal at home and go back for the afternoon lessons. Teachers should promote a cordial relation with girls in primary schools. This can be through regular guidance and counselling programs, involvement of girls in activities and rewarding them where necessary. This will increase their stay in school. Primary schools should ensure that there are sufficient sanitation facilities for both girls. They need safer and secure sanitation facilities to enable them to stay in school. Parents should take their girls to study in schools that are easily accessible. This will reduce risks associated with moving long distances. Girls will be able to stay in school.